Analysis of the effects of six-month step aerobics programme with female students who train and female students who do not have organized physical training - Natalija Kurtović (SportLogia, 2016)
n a sample of 100 female students at the College of Nursing Studies of the University of Bihać, a six-months-long experiment was conducted with the aim of determining the differences between two groups, namely the one that practiced step aerobics twice a week and the other, control group, which had no organized physical training. The research topic is a longitudinal study on a sample of female students, through the prism of researching the efficiency of Step aerobics programme in the evaluation of selected anthropological characteristics, as well as through the process of valorization of this programme’s effect on the anthropological status of female students compared to students who did not have an organized physical training. Based on t-test and discriminant analysis, it has been concluded that there are statistically significant differences between these two groups of students. The results show that there has been a change in the students of the experimental group in the initial and final measurement, which also reflected on the differences between the experimental and control groups. A single discriminant function that has very high statistical significance has been isolated. Based on these results, it can be confirmed that there was an improvement of results of morphological characteristics in female students, although they practiced only twice a week. It turned out that there was also a redistribution of body composition on account of improving the volume at the expense of adipose tissue.